Comparing fine motor performance among young children with autism spectrum disorder, intellectual disability, attention-deficit/hyperactivity disorder, and specific developmental disorder of motor function - Lin, Ling-Yi; Hwang, I-Ting; Hsu, Chia-Fen; Yu, Wen-Hao; Lai, Pei-Chun; Chen, Yi-Wen; Tu, Yi-Fang (Frontiers in Pediatrics, 2024)
Objective: The acquisition of fine motor skills is considered to be a crucial developmental milestone throughout early childhood. This study aimed to investigate fine motor performance among young children with different disability diagnoses.Methods: We enrolled a sample of 1897 young children under the age of 6 years old who were at risk of developmental delays and were identified by a transdisciplinary team. A series of standardized developmental assessments included the Bayley Scales of Infant Development-Third Edition, Wechsler Preschool and Primary Scale of Intelligence-Fourth Edition, Peabody Developmental Motor Scale-Second Edition, and Movement Assessment Battery for Children-Second Edition were used. Retrospective chart reviews were conducted on all children to identify specific developmental disorders. The number of Autism Spectrum Disorder (ASD), Intellectual Disability (ID), Attention Deficit/Hyperactivity Disorder (ADHD), Comorbidity, Motor Dysfunction, and Unspecified Developmental Delays (DD) were 363 (19.1%), 223 (11.8%), 234 (12.3%), 285 (15.0%), 128 (6.7%), and 590 (31.1%), respectively.Results: Young children with ID, Comorbidity, and Motor Dysfunction demonstrated significant difficulty in performing manual dexterity and visual motor integration tasks, and scored significantly lower in these areas than children with ASD, ADHD, and Unspecified DD. Additionally, fine motor performance was associated with cognitive ability in children with different disability diagnoses, indicating that young children showed better fine motor performance when they demonstrated better cognitive ability. Conclusion: Our findings support that differences in fine motor performance differ by disability type. Close links between fine motor performance and cognitive ability in children under the age of 6 were seen in all disability types.